Quantitative Trait Locus Mapping for Verticillium wilt Resistance in an Upland Cotton Recombinant Inbred Line Using SNP-Based High Density Genetic Map - Palanga, Koffi Kibalou; Jamshed, Muhammad; Rashid, Md. Harun or; Gong, Juwu; Li, Junwen; Iqbal, Muhammad Sajid; Liu, Aiying; Shang, Haihong; Shi, Yuzhen; Chen, Tingting; Ge, Qun; Zhang, Zhen; et al. (Frontiers in Plant Science, 2017)
Verticillium wilt (VW) caused by Verticillium dahlia Kleb is one of the most destructive diseases of cotton. Numerous efforts have been made to improve the resistance of upland cotton against VW, with little progress achieved due to the paucity of upland cotton breeding germplasms with high level of resistance to VW. Gossypium barbadense was regarded as more resistant compared to upland cotton; however, it is difficult to apply the resistance from G. barbadense to upland cotton improvement because of the hybrid breakdown and the difficulty to fix resistant phenotype in their interspecific filial. Here we reported QTLs related to VW resistance identified in upland cotton based on one year experiment in greenhouse with six replications and 4 years investigations in field with two replications each year. In total, 119 QTLs of disease index (DI) and of disease incidence (DInc) were identified on 25 chromosomes of cotton genome except chromosome 13 (c13). For DI, 62 QTLs explaining 3.7-12.2% of the observed phenotypic variations were detected on 24 chromosomes except c11 and c13. For DInc, 59 QTLs explaining 2.3-21.30% of the observed PV were identified on 19 chromosomes except c5, c8, c12-c13, c18-c19 and c26. Seven DI QTLs were detected to be stable in at least environments, among which six have sGK9708 alleles, while 28 DInc QTLs were detected to be stable in at least environments. Eighteen QTL clusters containing 40 QTLs were identified on 13 chromosomes (c1-c4, c6-c7, c10, c14, c17 c20-c22, and c24-c25). Most of the stable QTLs aggregated into these clusters. These QTLs and clusters identification can be an important step towards Verticillium wilt resistant gene cloning in upland cotton and provide useful information to understand the complex genetic bases of Verticillium wilt resistance.